Prospective Clinical Study with New Materials for Tissue Regeneration: A Study in Humans - Kollek, Nathalie Jeannette; Pérez-Albacete Martínez, Carlos; Granero Marín, José Manuel; Maté Sánchez de Val, José Eduardo (European Journal of Dentistry, 2022)
Objective This study was performed to evaluate the clinical, radiographic, and histomorphometric outcomes of novel bone grafting materials and dental membranes and to compare the results with current data from the literature.Materials and Methods New synthetic bone substitutes, consisting of biphasic calcium phosphate in the ratio of 60% hydroxyapatite and 40% β-tricalcium phosphate, were applied in bony defects and covered by either a novel synthetic poly(lactic-co-glycolic) acid (PLGA) or porcine collagen membrane. A sample of 51 biomaterials was placed in a total of 20 patients during different surgical protocols. Implants were simultaneously inserted, and in the case of sinus floor elevations 6 months later. Pre- and postoperative cone-beam computed tomographies were taken. Bone biopsies were harvested from augmented sides and processed for histomorphometric evaluation.Statistical Analysis Averages and ranges were calculated for the percentage of newly formed bone, residual biomaterial, and connective tissue. Data were submitted to analyze the radiological mean differences in length, width, and density. Paired t-tests were deployed for the analysis of differences within each group between the baseline (preoperative) and the final (postoperative) measurements.Results The mean bone gain in length and width were 0.96 ± 3.33 mm (+27.59%) and 1.22 ± 1.87 mm (+30.48%), respectively. The bone density was increased by a factor of 4, reaching an average of 387.47 ± 328.86 HU. Histomorphometric evaluations revealed new bone formation of 41.44 ± 5.37%, residual biomaterial of 24.91 ± 7.31%, and connective tissue of 33.64 ± 4.81%. The mean healing period was 8.32 ± 3.00 months.Conclusions Data from this study confirmed the suitability of the tested materials in dental surgery. The biomaterials may be recommended for various clinical procedures. A satisfactory level of increase of new bone was reported in augmented sides. No significant differences were observed between the tested membranes. PLGA membranes might be superior to collagen membranes for their easier handling.
Keywords: bone graft substitute; calcium phosphate; biomaterials; PLGA membrane; collagen membrane; osteointegration